FKA townhall session - UiTM, Fakulti Kejuruteraan Awam (Faculty of Civil Engineering, 2025)
The FKA Townhall Session was successfully conducted to deliver the latest updates on faculty affairs, strategic directions, and to strengthen two-way communication between the management and faculty members. The program began with registration and arrival, followed by a prayer recital and a safety video presentation. The session was officially opened with welcoming remarks by Prof. Ir. Ts. Dr. Che Khairil Izam Che Ibrahim, Dean of FKA, who emphasized the importance of continued collaboration and shared commitment in achieving the faculty's aspirations. S F Univ Presentations were delivered by key unit heads as follows: HEA Unit (Academic Affairs) - Presented by on behalf of the Deputy Dean (Academic), Assoc. Prof. Ir. Gs. Dr. Norashikin Ahmad Kamal covering program updates and academic quality. Shift today. HEP Unit (Student Affairs) - Presented by the Deputy Dean (HEP), Assoc. Prof. Ir. Ts. Dr. Norbaya Hj Sidek highlighting student welfare initiatives and support mechanisms. PJI Unit (Research & Industry Network) - Presented by the Deputy Dean (Research), Assoc. Prof. Ir. Ts. Dr. Mohd Khairul Kamarudin focusing on grants, publications, and industry collaborations.